Optimal price strategy for dual-channel retailer under different channel power structures. (2nd July 2016) - Zhang, Peng; He, Yong
Abstract: With the development of e-commerce, the more and more bricks-and-mortar retailers begin to develop online channel in addition to their existing traditional channel. In this paper, we use the Nash and Stackelberg game to examine the optimal decisions for such dual-channel supply chain under three kinds of power structures: balance power between the retailer and manufacturer, retailer-leader and manufacturer-leader, and obtain the equilibrium solutions of prices. We find that the impact of the acceptance of the online channel on the channel price strategy is greater than other parameters and there exists a unique and same threshold under the three kinds of power structures. When the value of acceptance of the online channel equals the threshold, decision-maker should adopt 'same product same price' strategy; when the value is lower or higher than the threshold, decision-maker should adopt 'same product different price' strategy. We then compare the equilibrium prices and profits under the three kinds of power structures. Lastly, to further understand the impact of the market environment and product cost on the prices and profits, we use analytical and numerical studies to carry on sensitivity analysis.